Can Africa Achieve Open Border Migration? - Ovett Nwosimiri (Global justice: Theory, Practice, Rhetoric)
Globally, the population of the African continent is increasing at the highest rate, and intracontinental migration is also increasing. Africans are moving more frequently inside their own continent for social, political, medical, and economic reasons and sometimes safety. Given the significance of intracontinental mobility, the African Union has suggestedan open border or borderless Africa with seamless intracontinental migration. Therefore, in this paper, I seek to advance the arguments that question the viability of open border migration in Africa. My task follows two main lines of reasoning. (1) Using Bernard Matolino and Wenceslaus Kwindingwi’s views on Ubuntu, I seek to show how the issue of xenophobia that many Africans encounter on the continent would prevent the goal of openborder mobility from being successful. In light of the various xenophobic atrocities in South Africa, I question the relevance of Ubuntu, which stands for shared, reciprocal humanness and a strong sense of community that is also welcoming to migrants. In response, I question Ubuntu’s significance amid these xenophobic attacks and its utility once the open border policy is put into place. (2) I seek to question the merits and benefits of open borders for immigration to some African nations that are experiencing (ethnic) conflicts and wars. I will show that even if open borders for migration are made possible, many migrants’ lives will be lost and many nations will be in disarray (if not destroyed) if the continent fails to adequately address and provide practical solutions to xenophobic attacks, (ethnic) conflicts, and wars.